Novi pristopi, stare zablode - Virk, Tomo (Primerjalna književnost, 2009)
This article treats the chief collection of international comparative literature, "A comparative history of literatures in European languages", in the form of a "case study" - namely, the volume Romantic prose fiction. It demonstrates that the difficulties that have accompanied this project spanning several decades are of two types: conceptual and ideological (or pragmatic). The greatest obstacle to carrying out the project is a prevailing western-centrism and conceptual uncertainty. The article suggests how it is possible to overcome both obstacles.
Keywords: primerjalna literarna veda; evropske književnosti; history of literature; literarna zgodovina; Romanticism; romantika; evropocentričnost